Room for manoeuvre of economic policy in EU countries are there costs of joining EMU? - Helene Schuberth (Oesterreichische Nationalbank (OeNB), 1998)
Costs of a monetary union are typically analysed in the context of the optimum currency area approach, looking at the likelihood of asymmetric real disturbances, the degree of real wage flexibility and of labour mobility. But it is also important to consider the leeway of monetary and fiscal policy to respond to country-specific real shocks prior to entering the monetary union. Applying a structural VAR model to Austria, the Netherlands, Belgium, Sweden, Finland, Italy, United Kingdom, France and Spain indicates that costs of giving up autonomous monetary policy in a European Monetary Union (EMU) would generally not be too high. However, in Belgium, Finland, Italy, France and Spain autonomous monetary policy has shown positive short-run output effects in the past, in all other countries such effects are negligible or not significant. Some cushioning influence of adverse EMU effects, then, could be expected from autono-mous fiscal policy measures, since results suggest that autonomous fiscal policy had positive short-run output ratio effects in the past, those effects being pronounced in Sweden, Finland, United Kingdom and France. It is also shown that autonomous monetary and fiscal policy were both capable of dampening country-specific business cycles. Consequently, EMU could reduce the degree of synchronisation of output fluctuations across Europe.
Keywords: 330